Students’ Experiences with Discord-Supported Critical Listening Instruction - Mubarok, Harir (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2026)
The increasing popularity of the internet has prompted people to embrace digital platforms for language acquisition. Language environments currently exist in both classrooms and virtual spaces. Therefore, listening skills, which are an important feature of language proficiency, especially in higher education, can be taught through a medium called Discord as a new and useful digital learning tool. The primary aim is to dig further the students’ voices to enhance listening proficiency skills. To gather this meaningful data, descriptive qualitative design involves the instruments of classroom observation checklist, field notes, and Focus Group Discussion (FGD). Additionally, this study focused on the 20 students enrolled in the International Class Program at Maulana Malik Ibrahim Islamic State University Malang. The findings revealed that Discord facilities the systematic materials, allow features for supporting offline and online class, design the new interactive educational agendas, and immediate response in Discord facilitates dynamic discussions.